Biopolymers from Natural Resources - Balart Gimeno, Rafael Antonio; Arrieta Dillon, Marina Patricia; García García, Daniel; Quiles Carrillo, Luís Jesús; Borrás, Vicent Fombuena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This work covers all aspects related to the obtainment, production, design, and processing of biopolymers obtained from natural resources. Moreover, it studies characteristics related to the improvement of their performance to increase their potential application at an industrial level, in line with the concept of a global circular economy. Thus, this work firstly classifies biopolymers obtained from natural resources (e.g., biobased building blocks and biopolymers extracted directly from plants and biomass), and then summarizes several cutting-edge research works focused on enhancing the performance of biopolymers from natural resources to extend their application in the industrial sector, and contribute to the transition to more sustainable plastics.